A spiking Basal Ganglia model of synchrony, exploration and decision making - Mandali, Alekhya; Rengaswamy, Maithreye; Chakravarthy, V. Srinivasa; Moustafa, Ahmed A. (Frontiers in Neuroscience, 2015)
To make an optimal decision we need to weigh all the available options, compare them with the current goal, and choose the most rewarding one. Depending on the situation an optimal decision could be to either ‘explore’ or ‘exploit’ or ‘not to take any action’ for which the Basal Ganglia (BG) is considered to be a key neural substrate. In an attempt to expand this classical picture of BG function, we had earlier hypothesized that the Indirect Pathway (IP) of the BG could be the subcortical substrate for exploration. In this study we build a spiking network model to relate exploration to synchrony levels in the BG (which are a neural marker for tremor in Parkinson’s disease). Key BG nuclei such as the Sub Thalamic Nucleus (STN), Globus Pallidus externus (GPe) and Globus Pallidus internus (GPi) were modeled as Izhikevich spiking neurons whereas the Striatal output was modeled as Poisson spikes. The model is cast in reinforcement learning framework with the dopamine signal representing reward prediction error. We apply the model to two decision making tasks: a binary action selection task (similar to one used by Humphries et al. 2006) and an n-armed bandit task (Bourdaud et al. 2008). The model shows that exploration levels could be controlled by STN’s lateral connection strength which also influenced the synchrony levels in the STN-GPe circuit. An increase in STN’s lateral strength led to a decrease in exploration which can be thought as the possible explanation for reduced exploratory levels in Parkinson’s patients. Our simulations also show that on complete removal of IP, the model exhibits only Go and No-Go behaviors, thereby demonstrating the crucial role of IP in exploration. Our model provides a unified account for synchronization, action section, and explorative behavior.